2014
DOI: 10.11646/zootaxa.3847.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Galkinius nom.nov., replacement name for Galkinia Ross & Newman, 1995

Abstract: In 1995, Ross & Newman proposed Galkinia as a replacement name for Utinomia Galkin, 1986 (Cirripedia: Pyrgomatidae), which was pre-occupied. However, this author discovered Galkinia was itself pre-occupied by a genus of fossil fish, Galkinia Ghekker, 1948 (Actinopterygii: Pholidophoriformes).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ross & Newman () indicated that the name Utinomia is pre‐occupied and proposed Galkinia as a replacement. However, Perreault () discovered that Galkinia was itself pre‐occupied and replaced it with Galkinius.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ross & Newman () indicated that the name Utinomia is pre‐occupied and proposed Galkinia as a replacement. However, Perreault () discovered that Galkinia was itself pre‐occupied and replaced it with Galkinius.…”
Section: Introductionmentioning
confidence: 99%
“…Ross & Newman (1995) indicated that the name Utinomia is pre-occupied and proposed Galkinia as a replacement. However, Perreault (2014) discovered that Galkinia was itself preoccupied and replaced it with Galkinius. Ross & Newman (2002), in an updated nominal list of coral-inhabiting barnacles, based on earlier studies, allocated the pyrgomatids with four shell plates and fused scutum and tergum to two genera, the monospecific Creusia and Galkinius with four nominal species.…”
Section: Introductionmentioning
confidence: 99%
“…Ross and Newman (1995) renamed Utinomia as Galkinia , and designated G. indicum (Annandale, 1924) as the type species. Perreault (2014) pointed out the generic name Galkinia Ross & Newman, 1995 was preoccupied by a genus of fossil fish, Galkinia Ghekker, 1948 (Actinopterygii: Pholidophoriformes). He therefore renamed Galkinia as Galkinius Perreault, 2014, thereby continuing to recognize Galkin’s contribution to cirripede taxonomy.…”
Section: Introductionmentioning
confidence: 99%